2015
DOI: 10.4209/aaqr.2014.10.0264
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Emission of Polybrominated Dibenzo-p-dioxins and Dibenzofurans from Converter Steelmaking Processes

Abstract: Polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs) and polybrominated diphenyl ethers (PBDEs) were characterized and quantified in stack gas from secondary ventilation systems from five different steelmaking plants. The concentrations of 2,3,7,8-substituted PBDD/Fs (2,3,7,8-PBDD/Fs) and PBDEs were 0.036-0.19 ng/Nm 3 (0.32-4.33 pg toxic equivalency (TEQ)/Nm 3 ) and 3.11-40.0 ng/Nm 3 , respectively, in the stack gas. These concentrations were lower than those in other metallurgical processes, such as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…It should be noted that PBDE emissions from stationary and mobile combustion sources to the atmosphere were not included in the PBDE inventory of Schenker et al (2008). (Odabasi et al, 2009;Wang et al, 2010a, b, c;WyrzykowskaCeradini et al, 2011;Liao et al, 2012;Chang et al, 2013bChang et al, , 2014bDrage et al, 2014;Li et al, 2015;Tsai et al, 2016;Chen et al, 2017;Li et al, 2017). Combustion sources possess high PBDE concentrations in the flue gases/exhaust (one to three orders higher than those in indoor and workplace air), huge flue gas flow rates and numerous amounts (e.g., vehicles), revealing their importance on contributing significant PBDEs to the atmosphere (Wang et al, 2010b).…”
Section: Global Pbde Evaporative and Fugitive Emissionsmentioning
confidence: 99%
“…It should be noted that PBDE emissions from stationary and mobile combustion sources to the atmosphere were not included in the PBDE inventory of Schenker et al (2008). (Odabasi et al, 2009;Wang et al, 2010a, b, c;WyrzykowskaCeradini et al, 2011;Liao et al, 2012;Chang et al, 2013bChang et al, , 2014bDrage et al, 2014;Li et al, 2015;Tsai et al, 2016;Chen et al, 2017;Li et al, 2017). Combustion sources possess high PBDE concentrations in the flue gases/exhaust (one to three orders higher than those in indoor and workplace air), huge flue gas flow rates and numerous amounts (e.g., vehicles), revealing their importance on contributing significant PBDEs to the atmosphere (Wang et al, 2010b).…”
Section: Global Pbde Evaporative and Fugitive Emissionsmentioning
confidence: 99%
“…The PBDD/Fs can be compared with the PCDD/Fs, but less concern has been expressed about the presence of PBDD/Fs in the environment than about the presence of PCDD/Fs, and very little information is available on PBDD/F concentrations in the environment. Previously published studies of PBDD/Fs in the environment have mainly been focused on the sources of PBDD/F emissions, such as electronic waste incineration processes (Duan et al, 2011), municipal waste incinerators (Wyrzykowska et al, 2009;Gullett et al, 2010) and metallurgical processes (Wang et al, 2010;Li et al, 2015b;Wang et al, 2015). Few studies of PBDD/Fs in the ambient air have been carried out in recent years (Li et al, 2008a;Li et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The inverse result was reported in a recent Chinese study, which revealed that PBDE concentrations in outdoor air in a community in Gungzhou in the Pearl River Delta (PRD) were notably higher than those in indoor air (Ding et al, 2016). Extremely high levels of PBDEs in the indoor and outdoor air have also been found in e-waste workplaces steelmaking plants and dismantling areas (Hearn et al, 2012;Tue et al, 2013;Ren et al, 2014;Li et al, 2015;Xu et al, 2015). Workers near an automotive shredding and metal recycling plants were assessed to be two times higher to be likely to be exposed to PBDEs compared with Australians in their home environments (Hearn et al, 2012).…”
Section: Introductionmentioning
confidence: 49%